Digital Health Opportunities and Risks: The Psychological Field - Mercurio, Simona; Mango, Lucio (Journal of Community Medicine and Health Solutions, 2023)
The digital transformation in the health sector represents an extraordinary challenge not only concerning patient care and assistance processes but also for the purpose of promoting new models capable of responding to the growing complexity of the environment and its impact on health. Psychological services are among the non-medical healthcare services heavily invested by this radical transformation. The constant increase in online psychology demand by users follows the need to carefully regulate its practice since this digital space, virtually a non-place, is the focus of large commercial interests. Being a part of the application of digital technologies to psychological performance, the aim of the paper was to emphasize clinical work, especially focused on childhood and adolescence with the need of identifying the limits and problems of digital health psychology in this group of subjects. Considering also that the massive use of digitization in healthcare also raises considerations of a bioethical nature regarding the priority of the principle of patient autonomy in the complex and articulated process of healthcare and protection. In conclusion, although TM is spread in our area in an uneven way, the representations of TM are mostly positive. However, it seems to emerge a picture in which part of some professionals still look to be too cautious and resist this new way.